Long-term back pain recall in Generation XXI adolescents: the role of sensitivity and pain history - Nare Navasardyan; Ana Henriques; Sónia Bernardes; Elsa Mateus; Makram Talih; Raquel Lucas (PAIN Reports)
Abstract. Introduction:. Adolescence is a period of profound cognitive and affective development, making it a critical period for studying pain memory and its role in chronic pain. Objective:. As this issue is underexplored in adolescents, we aimed to quantify the long-term back pain recall and assess its association with other pain-related factors and experiences. Methods:. We analyzed data of 1,089 participants from the Generation XXI birth cohort (Portugal), comparing back pain reported at age 13 (Lübeck Pain-Screening Questionnaire) to recalled back pain at 18 (explicit pain memory), investigating instances of forgetting/under-recalling, over-recalling, concordantly recalling presence/absence of back pain. We combined concordant recalls into a single category and under-recalling and over-recalling of any back pain as instances of discordant recall. Parameters such as current pain, family members with recurrent pain, health-related quality of life, environmental sensitivity, and self-perceived pain sensitivity were analyzed. Results:. At age 18, a small percentage of participants recalled experiencing back pain at age 13, while 12% under-recalled it. Concordant recall was significantly higher in boys (OR: 1.62; 95% confidence interval [CI]: 1.20–2.19) and individuals with higher environmental sensitivity (OR: 1.74; CI: 1.07–2.85). Those experiencing current pain were less likely to under-recall compared with those without current pain (OR: 0.21; CI: 0.05–0.91). A good health-related quality of life increased the likelihood of under-recall (OR: 2.91; CI: 1.11–7.67) but did not significantly affect over-recall. Conclusion:. Our results suggest that pain history and sensitivity significantly influence recall, which could contribute to pain experiences later in life.